A hidronínimia da região do Rio das Velhas: de Ouro Preto ao Sumidouro - Leticia Rodrigues Guimaraes Mendes (2009)
The present essay aims the study of the hydronyms from the High and Middle Lands of Velhas River, a region which keeps deep relation with the occupation and settlement of the pioneer bandeirante in Minas Gerais territory. Our proposal is to demonstrate that the toponimical studies, including the ones related to the water universe, reveal a close relation among man, his culture and the environment where he is. As a theoretic-methodological reference we have adopted the concepts of Dauzat (1926), Dick (1990a and 1990b), concepts about culture, according to Diegues Junior (1960), and environment, according to Sapir (1964). Under the sociolinguistic perspective, according to the labovian model, we start from the present collecting contemporary data using cartographic maps from IBGE. Then we go back to the past to collect data in some topographic maps done between the 18th and 19th centuries, and we come back to the present in order to establish comparisons between the data from the past and the present, study the changes and retention in the names of the watercourses and create a glossary containing the collected watercourse names. The results obtained through our study showed the relation between man and the environment in Minas Gerais by the time of the bandeirantismo and also in several aspects which are present in contemporary times: names coming from physical nature were predominant, specially the ones related to plants (phyto toponyms), confirming the intense link that man establishes with nature elements when he is naming things.